1989
DOI: 10.1111/j.2042-3306.1989.tb04672.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of growth and regression of ovarian follicles during the oestrous cycle and after hemiovariectomy in mares

Abstract: Summary To increase our understanding of the regulation of ovarian follicular development during the oestrous cycle, 13 mares were used in two experiments. In Experiment 1, the pattern of growth and regression of individual follicles, 15 mm or more in size, was monitored daily during 17 oestrous cycles by real‐time ultrasonography. Each examination was recorded on videotape to ensure accurate monitoring of individual follicles. Results indicated that the development of such follicles occurs in waves, with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The causes of these relatively high levels of dioestrous follicular activity during the second half of the ovulatory season in Mangalarga mares are intriguing. Although differences between breeds with regard to patterns of follicular development have been well established (Sirois et al 1989;Ginther 1990;Ginther 1992;Plata-Madrid et al 1994), it is reasonable to suspect an influence of environment on ovarian activity in the Mangalarga mares used in the present study . Quintero et al (1995) studied seasonal changes in ovarian activity of Thoroughbred mares maintained in a tropical environment and suggested a direct relationship between latitude and seasonality, the closer the mare being to the Equator, the less seasonal her reproductive pattern.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The causes of these relatively high levels of dioestrous follicular activity during the second half of the ovulatory season in Mangalarga mares are intriguing. Although differences between breeds with regard to patterns of follicular development have been well established (Sirois et al 1989;Ginther 1990;Ginther 1992;Plata-Madrid et al 1994), it is reasonable to suspect an influence of environment on ovarian activity in the Mangalarga mares used in the present study . Quintero et al (1995) studied seasonal changes in ovarian activity of Thoroughbred mares maintained in a tropical environment and suggested a direct relationship between latitude and seasonality, the closer the mare being to the Equator, the less seasonal her reproductive pattern.…”
Section: Discussionmentioning
confidence: 85%
“…However, these findings disagreed with previous studies that had reported the presence of large follicles, and even the occurrence of ovulation during dioestrus, in some mares (Vandeplasche et al 1979). The discrepancy continued until Sirois et al (1989) and Ginther (1990) both reported 2 distinct patterns of follicular dynamics during the equine oestrous cycle. By repeated ultrasonographic monitoring of individual follicles these authors were able to identify cycles that contained one follicular wave and other cycles that contained 2 waves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, cultures of preovulatory follicles or isolated germinal vesicle-stage COCs with EREG or AREG induced cumulus expansion and oocyte meiotic resumption in a manner similar to that observed by LH/hCG in ovarian follicles in vivo [2,35,36]. To increase our understanding of EREG and AREG regulation in follicular cells of large monoovulatory animal species, the equine preovulatory follicle was selected as a model because of its large size (40-45 mm in diameter), protracted ovulatory process (39-42 h interval from hCG to ovulation) and ability to monitor preovulatory follicular development by ultrasonography [53]. The current study revealed the presence of a marked gonadotropin-dependent induction of EREG and AREG mRNAs in equine follicle prior to ovulation, with an induction observed in both granulosa and theca cells.…”
Section: Discussionmentioning
confidence: 99%
“…In cattle, one study using GnRH as an agonist revealed a significant induction of AREG transcripts in both granulosa and theca cells [27], whereas another investigation using differential display reverse transcription polymerase chain reaction analysis and suppressive subtractive hybridization showed the expression of EREG mRNA in granulosa cells of bovine follicles containing a competent oocyte [41]. The development of the equine preovulatory follicle is of particular interest because of its large size (40-45 mm), relatively long ovulatory process (defined as the interval of time from hCG administration to follicular rupture) and pattern of recruitment and selection, which resembles that observed in women [11,16,53]. Thus, the objectives of the present work were to characterize the gonadotropin-dependent regulation of EREG and AREG in equine follicles prior to ovulation and, using primary cultures of bovine granulosa cells, to document the effect of EGFR activation on the expression of ovulation-related genes in granulosa cells of a large monoovulatory animal species.…”
Section: Introductionmentioning
confidence: 99%